Thermal Confinement and Filtering Effect of SnSe by Insertion of Atomic-Layer-Deposited ZnO Interfacial Layer - Jung, Myeong Jun; Eun, Su Min; Kim, Hogyoung; Kim, Seong Keun; Byun, Jongmin; Choi, Byung Joon (한국화학공학회, 2025)
SnSe is a promising thermoelectric material with excellent performance, but its practical use is limited by poor mechanical properties and challenges in mass production. Improving polycrystalline SnSe has been the focus, with grain boundary engineering via atomic layer deposition (ALD) emerging as an effective approach. ALD introduces interfacial layers that reduce thermal conductivity through phonon scattering and enhance the Seebeck coefficient via energy-filtering effects. In this study, ZnO thin films were uniformly deposited on SnSe powders using ALD, and their microstructure and chemical properties were analyzed. Thermoelectric evaluations showed a 45% improvement in the figure of merit for ZnO-coated SnSe pellets. Transmission electron microscopy revealed that the thickness and crystallinity of the ZnO film play a critical role in enhancing thermoelectric performance, highlighting the importance of interfacial engineering for optimizing SnSe-based thermoelectric materials.